2022
DOI: 10.1002/jnr.25112
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine plays a critical role in the olfactory adaptive learning pathway in Caenorhabditis elegans

Abstract: Encoding and consolidating information through learning and memory is vital in adaptation and survival. Dopamine (DA) is a critical neurotransmitter that modulates behavior. However, the role of DA in learning and memory processes is not well defined.Herein, we used the olfactory adaptive learning paradigm in Caenorhabditis elegans to elucidate the role of DA in the memory pathway. Cat-2 mutant worms with low DA synthesis showed a significant reduction in chemotaxis index (CI) compared to the wild type (WT) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…In addition, dopaminergic neurons in C. elegans are responsible for adaptive learning and memory (Raj & Thekkuveettil, 2022). We found that olanzapine caused the degeneration of dopaminergic neurons in C. elegans.…”
Section: Olanzapine Accelerates Aging Via Defective Mitophagymentioning
confidence: 82%
See 3 more Smart Citations
“…In addition, dopaminergic neurons in C. elegans are responsible for adaptive learning and memory (Raj & Thekkuveettil, 2022). We found that olanzapine caused the degeneration of dopaminergic neurons in C. elegans.…”
Section: Olanzapine Accelerates Aging Via Defective Mitophagymentioning
confidence: 82%
“…As aforementioned, olanzapine caused cognitive decline during aging in C. elegans , therefore, we investigated whether olanzapine leads to the degeneration of dopaminergic neurons, which are critical for adaptive learning and memory (Raj & Thekkuveettil, 2022). The age‐dependent damage of dopaminergic neurons (four CEP neurons) in C. elegans was assessed using the transgenic strain expressing Pdat‐1::GFP (Beilina et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assay was performed by trapping the worms in a sodium alginate scaffold (Raj & Thekkuveettil, 2022).…”
Section: Methodsmentioning
confidence: 99%